EVACUATION ROUTE ANALYSIS AND ACTIVE FIRE PROTECTION SYSTEMAT UNIVERSITAS NEGERI PADANG - Eggy Arya Giofandi; Aesya Nida Avrila (Universitas Negeri Padang, 2021)
Attention and handling in disaster mitigation efforts. According to Law no. 24 of 2007 concerning Disaster Management, fires are categorized as natural disasters as well as non-natural disasters based on their causes. This indicates that fire disasters, apart from being affected by physical or natural conditions, can also occur due to human negligence as the cause. There are four fire safety components, namely fire protection facilities, fire engine access, life-saving facilities and Fire Safety Management Building (MKKG). Various fire incidents that occur can be caused by the absence or ineffective functioning of early detection systems, fire extinguishing systems and rescue systems. Therefore, it is important to know how to assess the availability of types of active fire protection system tools at the main campus of Universitas Negeri Padang as an effort to improve fire prevention and management. This study uses mixed methods (quantitative and qualitative) with a descriptive approach by determining the category of the condition level of the active protection system.